Aspectos epidemiológicos da Filariose Linfática Bancroftiana em antiga área endêmica da cidade de Salvador, Estado da Bahia - Alves, Verônica de Medeiros (2010)
The lymphatic filariasis, a disease known as elephantiasis in one of its chronic manifestations, is caused by a helminth nematodes species of Wuchereria bancrofti (Cobbold, 1877) that just parasite to human. It is transmitted by mosquitoes of the Culex quinquefasciatus (Say, 1823), with haematophagic nocturnal habit, which coincides with the peak of microfilariae in peripheral blood of the host. It is considered the second leading cause of the disability worldwide to work, to cause physical weakness, social stigma and economic loss. Is distributed in tropical and subtropical regions, present in 83 countries in Asia, Africa, Americas and Oceania, where an estimated 120 million in those infected. In Brazil, the areas considered at risk are the state of Pernambuco (Recife, Olinda, Jaboatão and Paulista), state of Alagoas (Maceió) and state of Pará (Belém), while the latter two cities with the foci of transmission interrupted. Salvador, capital of Bahia state, is considered the oldest focus of Bancroftian filariasis in Brazil. The first epidemiological survey conducted in the city to study the distribution of Wuchereria bancrofti was made in 1878, when 309 individuals were examined in 26 (8.4%) were found microfilariae in the blood. The last survey conducted in 1966 documented the prevalence found in the neighborhood Uruguay of 6.24%. Since then no study was conducted to evaluate the transmission of lymphatic filariasis in Salvador, the focus being considered extinct without any confirmation of the disposal of its transmission. The World Health Organization (WHO) established in 1997, the elimination of lymphatic filariasis in the world by the year 2020. In Brazil, in order to achieve this goal was established in 1997 in conjunction with the National Health Foundation, Research Institutes, Federal University of Alagoas and Health Departments of endemic areas, the National Plan to Eliminate Lymphatic Filariasis. Among the activities planned include the reassessment of epidemiological outbreaks considered extinct. This study aimed to evaluate the distribution of lymphatic filariasis endemic area in the old city of Salvador, Bahia (district and adjacent Uruguay). For this, we carried out the investigation in haemoscopic 11.324 students in the night time, finding no microfilaraemic; 663 employees and their families also underwent the examination of haemoscopia, not being found any microfilaraemic; researched is circulating antigens of W. bancrofti in 510 children aged 6 to 10 years of age through the immunochromatography test - ICT card, where no antigenemia was not identified; and determined the vector infection xenomonitoramento by using the technique of polymerase chain reaction, with the collection of 23.580 female mosquitoes of Culex quinquefasciatus that were engorged and resting inside houses. This analysis was not detected the presence of the DNA from W. bancrofti in these mosquitoes. These findings support that the elimination of the lymphatic filariasis transmission in the former endemic area of Salvador, Bahia and no expansion of lymphatic filariasis in areas adjacent to the old focus of Salvador.